PENERAPAN METODE FUZZY AHP DALAM PENENTUAN SEKTOR YANG BERPENGARUH TERHADAP PEREKONOMIAN PROVINSI BALI - ADNYANA, TJOKORDA GDE AGUNG FRISKA; GANDHIADI, G. K.; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 5 No 2 (2016)DO - 10.24843/MTK.2016.v05.i02.p122, 2016)
The aim of this research is to apply Fuzzy Analytic Hierarchy Process method to determine the dominant sectors of economy Bali Province. This research used survey data from respondents who understand about economy of Bali Province and Gross Regional Domestic Product (GRDP). The research variables consist of criteria and sub-criteria. The criteria consist of primary sector, secondary, and tertiary, while the sub-criteria consist of 9 sectors of the GRDP. Data processing is done by calculating the weighted average and arrange them into pairwise comparison matrices. Furthermore, the consistency ratio is checked. If consistency ratio less than 0.100 ( ), the elements of matrices is changed into triangular fuzzy scale and processed with synthetic extent to get the priority. Based on the result of research, the economy of Bali are dominated by tertiary sector in sector group, agriculture and forestry in sub-primary group, manufacturing industry in sub-secondary group, and trade, hotel and restaurant in sub-tertiary group.
Keywords: Economy, Sector, Fuzzy Analytic Hierarchy Process